CODE SWITCHING USED IN VLOGS BY INDONESIAN YOUTUBER “GEN HALILINTAR” - Nur Annisa Hafid; Sahril Nur (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This research discusses the code switching performed by Gen Halilintar. The aims of this study were (1) to identify the different types of code switching performed by Gen Halilintar based on their age variety, and (2) to examine the reasons for Gen Halilintar using those code switching based on their age variety. This research used a qualitative descriptive method by collecting data from the utterances of Gen Halilintar in their vlogs. Based on the data that has been collected and analyzed, it shows that the types of code switching used by teenagers and adults have similarities, namely: tag switching, intersentential switching, intra-sentential switching, conversational code switching, single word code switching, and integrated loanwords. While the motivational reasons using those code switching are interjection, repetition used for clarification, to soften or strengthen request or command, and because of real lexical need.